Democracy and liberalism: crisis, pathologies and resistance - Berekashvili, Bakar (The Copernicus Journal of Political Studies, 2018)
Liberal capitalist democracy is a universal socio-political project of our age. But this project is in crisis and in decline. The current crisis of democracy caused by the Darwinist spirit of the late capitalist order only proves that democracy is an instrument for strengthening the dominant positions of the ruling liberal elites. In other words, democracy, in particular liberal democracy as a hegemonic form of the contemporary global democratic project, functions as a formal ideological-instrumental framework for the reproduction of the dominant position of a ruling class serving the interests of the few, not the many. In this way, anti-democratic sentiments among the masses are fuelled almost everywhere in both Western and non-Western cultures where political elites have assumed a formal democratic mask. Furthermore, the existing crisis of the Western liberal democratic project has given crucial benefits for the revival of anti-elitist populism in the contemporary world. The goal of this paper is to critically examine the fate of democracy in modern times as well as to shed light once again on the crisis of the liberal conception of democracy, including its concomitant pathologies, resistances, and political and social consequences.